Existence and concentration of local mountain passes for a nonlinear elliptic field equation in the semi-classical limit - D’Aprile, Teresa (Topological Methods in Nonlinear Analysis, 2001)
In this paper we are concerned with the problem of finding solutions for the following nonlinear field equation -Δ u + V(hx)u-Δ_pu+ W’(u)=0, where u:R^N→ R^N+1, N≥3, p> N and h> 0. We assume that the potential V is positive and W is an appropriate singular function. In particular we deal with the existence of solutions obtained as critical (not minimum) points for the associated energy functional when h is small enough. Such solutions will eventually exhibit some notable behaviour as h→ 0^+. The proof of our results is variational and consists in the introduction of a modified (penalized) energy functional for which mountain pass solutions are studied and soon after are proved to solve our equation for h sufficiently small. This idea is in the spirit of that used in M. Del Pino and P. Felmer [< i> Local mountain passes for semilinear elliptic problems in unbounded domains< /i> , Calc. Var. Partial Differential Equations < b> 4< /b> (1996), 121–137], [< i> Semi-classical states for nonlinear Schrödinger equations< /i> , J. Funct. Anal. < b> 149< /b> (1997), 245–265] and [< i> Multi-peak bound states for nonlinear Schrödinger equations< /i> , Ann. Inst. H. Poincaré Anal. Non Linéaire < b> 15< /b> (1998), 127–149], where "local mountain passes" are found in certain nonlinear Schrödinger equations.